Fused triphenylamine moiety based fluorescence emitters for deep blue OLEDs with high luminance and low turn-on voltages. Issue 3 (12th January 2022) - Wu, Lijie; Xu, Jinhao; Zhang, Zewei; Xue, Wangjuan; Wang, Tao; Yan, Chaoyi; He, Junpeng; He, Yaowu; Yan, Hao; Meng, Hong
Abstract : The design of blue emitters is still desired for high performance organic light-emitting diodes (OLEDs). Abstract : The design of blue emitters is still desired for high performance organic light-emitting diodes (OLEDs). In this work, two blue emitters with a fused triphenylamine (FTPA) moiety, PIAN-FTPA and PI-FTPA, have been successfully synthesized and exhibited the desired deep blue emission both in solvents and thin films. Aiming at narrowing down the emission peak by the rigid structures of emitters, the devices fabricated with PIAN-FTPA and PI-FTPA achieve the same turn-on voltage of 2.8 V, and external quantum efficiencies (EQEs) of 5.74% and 4.17% with narrow full width at half maxima (FWHM) of 52 nm and 51 nm, respectively. In addition, the PIAN-FTPA device shows a maximum brightness of 24 000 cd m −2 and deep blue emission with a CIE coordinate of (0.15, 0.09). The high luminance and low turn-on voltages of the devices prove that FTPA derivatives can serve as new candidates for deep blue OLEDs.